2000
DOI: 10.1080/09535310050120952
|View full text |Cite
|
Sign up to set email alerts
|

A New Image of Classical Key Sector Analysis: Minimum Information Decomposition of the Leontief Inverse

Abstract: This paper provides a theoretical framework for the Rasmussen-Hirschman key sector analysis based on a minimum information approach. This approach introduces a separation of information about regional economic structure into two parts. In the first part, knowledge about economic structure, extracted on the basis of minimum information included in the row and column multipliers, is extracted from the Leontief inverse matrix. The second part presents the specifics of synergetic interactions between different sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 8 publications
0
50
0
1
Order By: Relevance
“…The additive features of these indirect and induced effects are compounded in the model through the Leontief Inverse Matrix [20]. The values in the Leontief Inverse Matrix represent the total direct and indirect requirements of any industry supplied by other industries within the region in order for that industry to be able to deliver US$1 worth of output to final demand [20]. Additional file 1 lists an example of some of the multipliers for Custer County.…”
Section: Economic Modelingmentioning
confidence: 99%
“…The additive features of these indirect and induced effects are compounded in the model through the Leontief Inverse Matrix [20]. The values in the Leontief Inverse Matrix represent the total direct and indirect requirements of any industry supplied by other industries within the region in order for that industry to be able to deliver US$1 worth of output to final demand [20]. Additional file 1 lists an example of some of the multipliers for Custer County.…”
Section: Economic Modelingmentioning
confidence: 99%
“…From the above Equations (1)- (6), it is clear that DIWDCs turn into IOO-TIWDCs through all sorts of linkages in a ij (or a pq ij ) and d ij (or d pq ij ). In input-output analysis, there are important linkages, including the backward linkage and the forward linkage, based on the Leontief inverse coefficients [52] . In later literature, some scholars differentiated the backward linkage from the forward linkage.…”
Section: Direct and Total Industrial Wastewater Discharge Coefficientmentioning
confidence: 99%
“…Recognizing industrial linkages as an important agglomeration factor in the industrial cluster, a growing number of economists have engaged in a variety of investigations seeking to document and substantiate the expected impacts, contributing to a wide range of academic disciplines and policy circles (Cella 1984;Parr 1999;Sonis, Hewings, and Guo 2000). A great many researchers, attempting to account for the regional and national agglomeration of economic activities, have suggested that selected regions-especially those in which industries are linked in transaction-intensive networks-are capable of exerting powerful push effects on national or regional economic development (Fujita and Thisse 2002;Krugman 1991Krugman , 1995Krugman and Venables 1996).…”
Section: Literature Reviewmentioning
confidence: 99%